2013
DOI: 10.1016/j.meegid.2013.04.028
|View full text |Cite
|
Sign up to set email alerts
|

SNP typing reveals similarity in Mycobacterium tuberculosis genetic diversity between Portugal and Northeast Brazil

Abstract: Abstract:Human tuberculosis is an infectious disease caused by bacteria from the Mycobacterium tuberculosis complex (MTBC). Although Spoligotyping and MIRU-VNTR are standard methodology in MTBC genetic epidemiology, recent studies suggest that Single Nucleotide Polymorphisms (SNP) are advantageous in phylogenetics and strain identification. In this work we use a set of 79 SNPs to characterize 1915 MTBC isolates from Portugal and 141 from Northeast Brazil. All Brazilian samples and a subset of 111 Portuguese is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
(54 reference statements)
4
11
0
Order By: Relevance
“…A large predominance of the MTBC L4 and of sublineage L4.3/LAM was revealed within the pathogen population ( Fig. 1e), in line with other reports focused in Europe 14,15 . The pathogen population structure was replicated across the different TB severity groups (Fig.…”
supporting
confidence: 91%
“…A large predominance of the MTBC L4 and of sublineage L4.3/LAM was revealed within the pathogen population ( Fig. 1e), in line with other reports focused in Europe 14,15 . The pathogen population structure was replicated across the different TB severity groups (Fig.…”
supporting
confidence: 91%
“…tuberculosis isolates, a total of 17119 (80.8%) strains belonged to lineage 4 (Euro-American) according to spoligotyping [ 56 ] ( Table 1 ). This widely predominant lineage supports the hypothesis of a European dissemination from either early settlement or trade associations [ 8 10 ]. Among the lineage 4 strains, a total of 6386 (30.1%) belonged to the LAM lineage; 4843 (22.9%) belonged to the T lineage; 3699 (17.5%) belonged to the H (Haarlem) lineage; 1564 (7.4%) belonged to the X lineage; 1163 belonged to the EAI lineage; 1105 belonged to the Beijing lineage; 497 (2.3%) belonged to the S lineage; 162 (0.8%) belonged to the CAS lineage; 102 (0.5%) belonged to the MANU lineage; 94 (0.4%) belonged to the AFRI lineage; 67 (0.3%) belonged to the Cameroon lineage and 63 (0.3%) belonged to the URAL lineage.…”
Section: Resultssupporting
confidence: 82%
“…The M . tuberculosis strains currently circulating in Americas were brought by Europeans with the Euro-American lineage 4 being the most predominant [ 8 ], highlighting past and present European colonial and cultural influence on the current TB situation [ 9 , 10 ]. Among the large and heterogeneous lineage 4, the Latin American Mediterranean (LAM) family was first suggested based on the phylogenetic analysis of a large spoligotyping dataset and its name reflects the strains’ origin [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several authors have suggested that SNPs are more suitable than spoligotyping and MIRU-VNTR settings for phylogenetic classification [16] , [38] , [53] , [54] , [55] , [56] . The fbpC 103 is described as a good marker for the LAM family [7] , [38] , [49] , [57] , [58] , [59] , and our original intention was to evaluate if strains RD Rio was still prevalent in Rio de Janeiro as seen previously by Lazzarini in clinical isolates collected between 2002 and 2003 [2] , for this purpose we believed only a marker that could differentiate LAM and non-LAM associated with the 24 MIRU-VNTR and Spoligotyping could be sufficient, however the scenario was observed more complex.…”
Section: Discussionmentioning
confidence: 99%